Who was Alexander Graham Bell? /Biography-Easy reader - Bader, Bonnie, 1961-; Groff, David, 1956- (New York, New York, USA : Grosset & Dunlap, an imprint of Penguin Group (USA) LLC, 2013)
"Did you know that Bell's amazing invention--the telephone--stemmed from his work on teaching the deaf? Both his mother and wife were deaf. Or, did you know that in later years he refused to have a telephone in his study? Bell's story will fascinate young readers interested in the early history of modern technology!"--
Who Was Alexander Graham Bell? -- An Inventor Is Born -- A Turning Point -- An Ear for Sound -- Endings and Beginnings -- A New Direction -- A Sound Is Heard -- A Race to the Finish -- Famous Words -- Victory! -- An Inventor to the End -- Timelines.
Includes bibliographical references (pages104-105)
Age 8 to 12.
Keywords: Bell, Alexander Graham, -- 1847-1922 -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Telephone -- United States -- Biography -- Juvenile literature; Biography-Easy reader